2016
DOI: 10.1136/svn-2016-000028
|View full text |Cite
|
Sign up to set email alerts
|

3D T1-weighted black blood sequence at 3.0 Tesla for the diagnosis of cervical artery dissection

Abstract: ObjectiveWe aimed to investigate the value of three-dimensional (3D) T1 volumetric isotropic turbo spin echo acquisition (VISTA) in the diagnosis of cervical artery dissection (CAD).MethodsWe prospectively included patients who were suspected as having a CAD within 1 month of onset. For T1 VISTA, the diagnosis of the dissection was based on the presence of intramural high-signal, intimal flap, double lumen and aneurysmal dilation. The final diagnosis of dissection was based on the clinical history, physical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…When dissection does not cause any alteration in the arterial lumen, it may lead to false negative in patients with CAD. A study shows that the 3D-T1 VISTA sequence is useful in the diagnosis of CAD it can show intramural hematoma of the cervical artery clearly [ 10 ]. It is worth pointing out that VW-MRI can not only display the lumen, but also image the vessel wall, it is helpful for further analyze the composition of plaque, judge the cause of stenosis and provide a direct imaging basis for clinical diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…When dissection does not cause any alteration in the arterial lumen, it may lead to false negative in patients with CAD. A study shows that the 3D-T1 VISTA sequence is useful in the diagnosis of CAD it can show intramural hematoma of the cervical artery clearly [ 10 ]. It is worth pointing out that VW-MRI can not only display the lumen, but also image the vessel wall, it is helpful for further analyze the composition of plaque, judge the cause of stenosis and provide a direct imaging basis for clinical diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In small feasibility studies, 3D T1 CUBE, 3D SNAP, and 3D T1 BB VISTA/SPACE were used to detect IMH, but these studies lacked comparison to 2D T1-weighted TSE and evaluation of IMH-related stroke. 28, 35, 36 While some studies have shown that 3D T1-weighted sequences can improve signal and contrast to noise ratios over 2D T1-weighted TSE, these again were too small to show significant improvements, and moreover did not evaluate stroke risk with IMH. 37, 38…”
Section: Discussionmentioning
confidence: 99%
“…Since no single reference standard for the diagnosis of CCAD was available, the final diagnosis results based on the clinical information, image data sets, and the results of follow-up were chosen to be the reference standard in the current study [ 20 - 22 ]. The final diagnosis of CCAD is a consensus of the attending neuroradiologists, neurosurgeries, and neurologists.…”
Section: Methodsmentioning
confidence: 99%